2010
DOI: 10.1016/j.febslet.2010.05.064
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Modulation of hypothalamic PTP1B in the TNF‐α‐induced insulin and leptin resistance

Abstract: a b s t r a c tWe have associated functional and molecular studies of insulin and leptin to investigate the effect of TNF-a on central insulin and leptin signaling in rats pre-treated with PTP1B-ASO. The icv infusion of TNF-a-induced an increase in PTP1B protein expression and activity, and attenuated insulin and leptin sensitivity and signaling in the hypothalamus. However, TNF-a was able to completely blunt the leptin and insulin effect in rats treated with PTP1B-ASO, suggesting that TNF-a does not require P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 36 publications
3
30
0
3
Order By: Relevance
“…Indeed, in a mouse model, Vijay-Kumar et al (15) reported that TLR-5 receptor impairment, involved in the bacterial flagellin recognition, led to a "human metabolic syndrome gut microbiota phenotype, " associated with low-grade inflammatory signals. In another study (16), the authors observed a metabolic syndrome after colonization of TLR-2 GF deficient mice, protected from diet-induced insulin resistance. The TLR-2 deficient mice became resistant to insulin and therefore obese, suggesting a correlation with the increased fat storage or with the augmented levels of gastrointestinal lipopolysaccharide (LPS) permeability and absorption.…”
mentioning
confidence: 98%
“…Indeed, in a mouse model, Vijay-Kumar et al (15) reported that TLR-5 receptor impairment, involved in the bacterial flagellin recognition, led to a "human metabolic syndrome gut microbiota phenotype, " associated with low-grade inflammatory signals. In another study (16), the authors observed a metabolic syndrome after colonization of TLR-2 GF deficient mice, protected from diet-induced insulin resistance. The TLR-2 deficient mice became resistant to insulin and therefore obese, suggesting a correlation with the increased fat storage or with the augmented levels of gastrointestinal lipopolysaccharide (LPS) permeability and absorption.…”
mentioning
confidence: 98%
“…We observed that single or repeated LPS treatment increased the PTP1B expression with a high colocalization with LepRbexpressing neurons in the hypothalamus. Changes in PTP1B expression have been shown to be induced by molecules such as tumor necrosis factor (TNF)␣ and nuclear factor-B (NF-B) (20,29,34,36,53), and LPS is known to induce the production of these molecules. Picardi et al (36) have demonstrated that central infusion of TNF␣ increased PTP1B protein expression and attenuated leptin sensitivity in the hypothalamus.…”
Section: E45 Leptin Resistance Induced By Long-term Exposure To Lpsmentioning
confidence: 99%
“…Moreover, dietinduced induction in proinflammatory cytokines triggers an immediate response in non-neuronal hypothalamic cells (microglial and astroglial populations) [33,36,37]. Corroborating a role for proinflammatory cytokines in leptin signalling pathology, central administration of TNF-α impairs leptin sensitivity, possibly by increasing the levels of SOCS3 and PTP1B, which act as negative regulators of leptin receptor signalling [9,11,38]. Although causality is not clear, there is considerable evidence to support the existence of a vicious cycle between excess nutrients, hypothalamic inflammation, leptin resistance and obesity [39].…”
Section: Targeting Leptin Responsiveness With Pharmacologymentioning
confidence: 99%
“…Indeed, preclinical studies have identified several 'leptin sensitisers', that may hold therapeutic promise. These leptin sensitisers target distinct neuroendocrine systems, all of which have been linked to leptin signalling pathology, including endoplasmic reticulum (ER) stress [8], hypothalamic inflammation [9] and multiple nodes of the leptin signalling cascade [10][11][12][13]. In addition, a growing body of evidence suggests that gastrointestinalderived peptides and a series of already approved pharmacotherapies can amplify the weight-lowering actions of exogenous leptin [14][15][16][17][18][19], re-positioning leptin as a relevant agent in combination therapies for the treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%